IDDF2019-ABS-0114 Role of linear endosonography in diagnosis of biopsy negative malignant esophageal strictures: exploring the unexplored. (7th June 2019) - Dahale, Amol; Srivastava, Siddharth; Sonika, Ujjwal; Dalal, Ashok; Goyal, Aditi; Sakhuja, Puja; Sachdeva, Sanjeev; Puri, Amarender
Abstract : Background: Endoscopic biopsy is standard for diagnosis of esophageal malignancy. However, few cases present with smooth stricture with repetitive negative biopsy results. We aimed to use linear endoscopic ultrasound (EUS) and fine needle aspiration (FNA) in diagnosis of biopsy negative suspected malignant esophageal strictures. Methods: We retrospectively analyzed the data from August 2017 to December 2018 of biopsy negative esophageal strictures. All adult patients with twice negative biopsies and having smooth overlying esophageal mucosa on endoscopy were included . Clinical, epidemiological, endoscopic, imaging and EUS findings were noted and analyzed. Results: Eighteen patients underwent EUS for suspicion of malignant esophageal stricture. Seven were excluded as they were submucosal tumors in which the role of EUS is already established . Eleven patients showed the presence of malignancy on EUS FNA samples. Nine were males. Computed tomography showed esophageal wall thickening in 8 (16–38 mm) and esophageal mass in 3 patients. EUS showed loss of normal five layered wall structure of esophagus in all patients. FNAC revealed squamous cell carcinoma (n=4), adenocarcinoma (n=4), poorly differentiated carcinoma (n=2) and neuroendocrine carcinoma (n=1).There were no complications. Conclusions: EUS with FNA is effective and safe for diagnosis of biopsy negative malignant esophageal strictures.